HSPA4 Expression is Correlated with Melanoma Cell Proliferation, Prognosis, and Immune Regulation - Wang X; Li Z; Xu J; Wang J; Li Y; Li Q; Niu J; Yang R (Dove Medical Press, 2024)
Xudong Wang,1- 3,* Zhiyong Li,1,* Jianhong Xu,1 Jun Wang,1 Ying Li,1 Qiang Li,4 Jianrong Niu,5 Rongya Yang2 1Outpatient Department of Yangfangdian, Southern Medical District of Chinese PLA General Hospital, Beijing, 100843, People's Republic of China; 2Department of Dermatology, Seventh Medical Center of Chinese PLA General Hospital, Beijing, 100010, People's Republic of China; 3Medical School of Chinese PLA, Beijing, 100853, People's Republic of China; 4Medical Health Care Dept, Air Force Medical Center PLA, Beijing, 100142, People's Republic of China; 5Department of Dermatology, Air Force Medical Center PLA, Beijing, 100142, People's Republic of China*These authors contributed equally to this workCorrespondence: Rongya Yang, Department of Dermatology, Seventh Medical Center of Chinese PLA General Hospital, Beijing, 100010, People's Republic of China, Email yangrya@sina.com Qiang Li, Medical Health Care Department, Air Force Medical Center PLA, Beijing, 100142, People's Republic of China, Email 16585260@qq.comPurpose: Heat shock protein A4 (HSPA4) is associated with a variety of human diseases. However, its function in cutaneous malignant melanoma (CMM) remains uncertain.Patients and Methods: The gene and protein expression level of HSPA4 in CMM was investigated with public databases. Cell Counting Kit-8 (CCK8) assay was performed to assess the effect of HSPA4 on the proliferation of melanoma cells. Then, the diagnostic and prognostic value of HSPA4 in CMM were analyzed. Gene variations and methylation levels, and the correlation between HSPA4 expression and immune cell infiltration were evaluated, followed by the construction of HSPA4 related protein-protein interaction networks and functional enrichment analysis.Results: The mRNA and protein expression level of HSPA4 was significantly higher in CMM. Knocking down HSPA4 in A-375 cell line could inhibit tumor cell growth. The receiver operating characteristic (ROC) curve analysis confirmed the diagnostic value of HSPA4. Survival analysis showed that high expression of HSPA4 was associated with poor prognosis. HSPA4 gene alterations were observed in 3% of CMM patients. Five CpG sites are associated with the prognosis of CMM. HSPA4 is negatively correlated with most immune cells in CMM. The protein interaction network shows that HSPA4 is closely related to proteins such as DnaJ heat shock protein family (Hsp40) member B1 (DNAJB1) and DnaJ heat shock protein family (Hsp40) member B6 (DNAJB6), and the expression of DNAJB1 is positively correlated with HSPA4. Functional enrichment analysis indicated that HSPA4 may be associated with immune suppression and immune escape within the tumor microenvironment of CMM.Conclusion: HSPA4 may participate in the regulation of tumor development and microenvironment, which may be a potential diagnostic and prognostic marker of CMM.Keywords: heat shock protein, melanoma, HSPA4, TCGA, bioinformatics